2015
DOI: 10.1016/j.socscimed.2014.06.047
|View full text |Cite
|
Sign up to set email alerts
|

Brief encounters: Assembling cosmetic surgery tourism

Abstract: This paper reports findings from a large-scale, multi-disciplinary, mixed methods project which explores empirically and theoretically the rapidly growing but poorly understood (and barely regulated) phenomenon of cosmetic surgery tourism (CST). We explore CST by drawing on theories of flows, networks and assemblages, aiming to produce a fuller and more nuanced account of - and accounting for - CST. This enables us to conceptualise CST as an interplay of places, people, things, ideas and practices. Through spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 20 publications
(22 reference statements)
0
34
0
1
Order By: Relevance
“…Trying to conform to these externally imposed beauty standards has created a significant boom in cosmetic surgery tourism. For example, the “Korean Look” is regarded as highly fashionable, and thus, numerous Chinese youth are attracted to South Korea for cosmetic surgery on their eyelids, nose, breasts, and so forth (Holliday, Bell, Cheung, Jones, & Probyn, ). As Viladrich and Baron‐Faust () argued, cosmetic surgery tourists are “a growing group of transnational patients who visit distant locations to improve their bodies while enjoying recreational activities” (p.119).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Trying to conform to these externally imposed beauty standards has created a significant boom in cosmetic surgery tourism. For example, the “Korean Look” is regarded as highly fashionable, and thus, numerous Chinese youth are attracted to South Korea for cosmetic surgery on their eyelids, nose, breasts, and so forth (Holliday, Bell, Cheung, Jones, & Probyn, ). As Viladrich and Baron‐Faust () argued, cosmetic surgery tourists are “a growing group of transnational patients who visit distant locations to improve their bodies while enjoying recreational activities” (p.119).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As indicated by Holliday et al (2015), Chinese adults have shown an increasing trend to pursue a better appearance through cosmetic surgeries. One popular destination for this is South Korea, which is one of the internationally recognized destinations that provide professional cosmetic surgery services (International Society of Esthetic Plastic Surgery, 2016; Kim, Lee, & Jung, 2013).…”
Section: Study Settingmentioning
confidence: 99%
“…Its use as a distinct ontology for tourism, and tourism places is in very early stages. Recent applications concern tourism, not tourism destinations directly (Anderson, ; Bell, Holliday, Jones, Probyn, & Taylor, ; Holliday et al, ; Mostafanezhad, ; Waitt & Duffy, ), adopt the Deleuzian approach but do not further employ assemblage as an analytic along the lines of AT as concisely articulated by DeLanda () and adopted by others (Anderson & McFarlane, ).…”
Section: Alternative Conceptions Of Tourism Destinationsmentioning
confidence: 99%
“…Building and real estate interests often catalyze the process as the emergence of regional level TAs in the Mediterranean and other world regions evinces. Presently, tourism entrepreneurs and intermediaries increasingly influence the formation of novel TAs such as cosmetic surgery and medical tourism, volunteer tourism, and others (Holliday et al, 2015;Mostafanezhad, 2014). More importantly, they shape the representation and determine the character and fate of destinations through marketing, social and discursive practices, and coding devices, producing particular discourses, narratives, and potted historical narratives that frame, inform, and influence tourist practices and performances (Edensor, 2000;Framke, 2002;Lew, Hall, & Williams, 2014 Thus, the emergence and cohesion of particular TAs is intentionally or unintentionally encouraged or discouraged.…”
Section: Tourism Entrepreneurs and Intermediaries Pursue Various Routinementioning
confidence: 99%
See 1 more Smart Citation